Efek Jamur Mikoriza Glomus intraradices terhadap Pertumbuhan Tagetes erecta L. pada Media Tanam Mengandung Kromium - Wartanto, Jokosulistyo; Kasmiyati, Sri; Bety E.K, Elizabeth (Bioedukasi: Jurnal Pendidikan Biologi, 2020)
Tagetes erecta is an annual plant that is, in addition, to be used as an ornamental plant, it can also be used as an agent for phytoremediation. Glomus intraradices is one of the species of vesicular-arbuscular mycorrhizal (VAM) fungi which can be mutually symbiotic with various species of plants, including T. erecta.  This study was aimed to determine the effect of VAM fungi G. intraradices on the growth of T. erecta in growth media containing chromium. The study was carried out experimentally using a completely randomized design with treatments, namely Cr6+ concentrations of 0, 5 and 10 ppm in the form of K2CrO7, and the addition of VAM fungi G. intraradices in the growth media in the form of soil and mixture of soil: textile sludge (1: 1).  T. erecta was grown in four different growth media (soil, soil: textile sludge (1:1), soil+VAM, soil: textile sludge (1:1)+VAM) that was treated with Cr6+ and G. intraradices for 1.5 months. The growth of T. erecta was determined based on plant height, root length, root dry weight, shoot dry weight, and percentage of mycorrhizal infection. Data were analyzed with two-way Analysis of Variance (two-way ANOVA) and DMRT (Duncan's Multiple Range Test) with a test level of 5%. The results showed that the growth of T. erecta in media containing Cr6+ (5 and 10 ppm) decreased significantly compared to controls (without Cr6+ treatment).  The highest reduction of plant growth was found in media containing Cr6+ of 10 ppm. The addition of VAM fungi G. intraradices in soil media and soil: textile sludge that treated with Cr6+ was able to increase the growth of T. erecta. These results indicated that the VAM fungi G. intraradices were able to improve the ability of T. erecta to deal with chromium heavy metal stress. That results were also supported by the percentage of mycorrhizal infection in the roots of T. erecta grown in soil and soil: textile sludge (1:1) media with treatments of Cr6+ and VAM G. intraradices were higher than the control plants that was grown in soil and soil: textile sludge (1:1) media without treatments of Cr6+ and VAM G. intraradices.